Productive consumption and economic communications - R. Valenčík; S. Sazanova; B. Yerznkyan; G. Ryazanova (Путеводитель предпринимателя)
Modern economic theory cannot overcome the neoclassical dichotomy «producer - consumer», which contradicts the principle of methodological atomism and therefore is a methodological problem. The authors found that the producer-consumer dichotomy is partially solved with the help of theoretical tools such as the equilibrium approach and the balance method, but this is not a methodological solution. The authors proved that the solution to the producer-consumer dichotomy can be a synthesis of the theory of productive consumption and the theory of economic communications.